Efficient Penetration Resolving in Multi-layered Virtual Dressing Based on Physical Method (Journal of Fiber Bioengineering and Informatics, 2015)
Around the research of garment simulation, multi-layered virtual dressing is still a difficult issue, one bigreason is that the effect of penetration always appears between adjacent garments at the beginning of thevirtual dressing with existing garments. In this paper, a simple system for physical based multi-layeredvirtual dressing is designed. At the same time, a novel method for efficiently resolving the penetrationproblem appeared between multi-layered garments during simulating is presented. Of the method, afilter algorithm for identifying penetration points during collision detection is provided. The experimentresults show that this method is practical and easy-use with generating realistic effects.